Application of wireless audio transmission circuit using laser technology - KARAARSLAN, Ahmet; ÖZER, Tolga (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
In technology, we see major innovation and improvements in our daily tools and machines. Meanly, technology is in constant race to get better than yesterday. It has been amazing upwards trend in technology over last 20 years to the level of „space time”. One of the major technology development areas are in the laser field. Although laser technology has been out there for many years, we have seen tremendous new laser applications recently. We are taking advantage of laser technology in all aspects of our life. As long as we use its precise and right parametric range, we get very valuable results. In this study, general information about lasers and laser wireless audio transmission circuit application was designed.